Bodysuit yourself: But first think about it - Sanders, R.; Rushall, B.; Toussaint, H. M.; Stager, J. M.; Takagi, H. (Journal of Turbulence, 2001)
The swimming attire worn at the recent 2000 Olympics is of interest from a fluid dynamics perspective. In previous Olympics, the application of ideas from fluid dynamics has played an important role in performance improvements in various sports. In the 2000 Olympics the issue of 'hydrodynamic' bodysuits 'made a splash'. While there is little doubt that advancements from a clever application of fluid dynamics has improved performance in sports such as cycling and flat-water kayak racing, the 'jury is still out' with respect to 'hydrodynamically' designed swimsuits. At the 2000 Olympics, gold medals were won with and without the new swimsuits, with varying degrees of use, and in their various forms. One is left unsure of whether these suits actually improve performance. Seeking a scientific basis for why they should or should not have an effect could provide answers. This article reviews theoretical aspects, the scientific rationale underlying design, scientific evidence relating to the actual effects, and some alternative explanations for benefits or decrements in performance that may be attributable to the suits. It is not written because the answers to many questions are known. Rather, it is an exploration of what should be considered.